Assertiveness Among Nursing Students Of A Nursing Institute In Kathmandu - Rana, Shristi (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Assertiveness is a key attribute for successful nursing practice. A professional nurse must be assertive for improving nursing care so it should be emphasized during their academic period. The objective of the study was to find out the assertiveness among nursing students in Kathmandu. Method: A descriptive cross-sectional study design with 71 nursing students of Proficiency Certificate Level (PCL) in Manmohan Memorial Institute of Health Sciences was conducted between 27th April, 2022 to 27th May 2022. Non-probability sampling technique was used to select the sample. Assertiveness Scale of Begley and Glacken, a self-administered questionnaire was used for data collection which was distributed to the respondents by mail. Data analysis and interpretation was done using descriptive and inferential statistics. Result: The result showed that majority of the respondents (87.3%) had moderate level of assertiveness and very least respondents (4.2%) had high level of assertiveness. Respondents were found to be more assertive who enjoy to start conversations with strangers (3.75±0.61), who are always frank about their feelings (3.57±0.92) and never find difficult to compliment and praise friends (2.97±1.01). However, they were less assertive in trying to avoid conflict (1.45±1.41), never disagree when a friends’ opinion is wrong (1.63±1.00) and are more careful to avoid hurting other people’s feelings (1.24±0.68). There is no significant association between level of assertiveness with sociodemographic variables. Conclusion: The findings of the study conclude that the majority of respondents were less assertive in avoiding conflict, disagreeing to friends’ opinion and careful to avoid hurting other people’s feeling. So, the concerned academic organization should emphasis more on encouraging assertiveness among the nursing students.